Tanfīżu Istirātījiyyati Mubārāti Biṭāqati al-Fahrasi li Tarqiyati Natāiji Ansyiṭati Ta’līmi al-Lugati al-`Arabiyyati bi al-Madrasati - Dedi Mulyanto; Febriansyah Harma; Muhammad Nadzif Safwan Bin Abu Bakar (Universitas Pendidikan Indonesia (UPI), 2022)
The objectives of this study are divided into two things: a) to increase the learning activeness and b) to improve the learning outcomes of class 1A students using the index card match learning strategy in Arabic lessons at the KH. Syamsuddin durisawo ponorogo Islamic boarding school. This type of research is called